2016
DOI: 10.7860/jcdr/2016/20759.9081
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter Meningitis and Challenges in Treatment

Abstract: Neurosurgical interventions are rarely associated with meningitis with a very low incidence rate ranging from 1.1% to 2.5%. Gram negative bacillary meningitis first described in the 1940's, previously uncommon has been increasing in the recent past associated with advanced age, immunosuppression and neurosurgery. meningitis though relatively uncommon is recently increasing in incidence and treatment is frequently complicated due to resistance to antibiotics making this a challenging, difficult to treat infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Another Gram-negative bacteria, Enterobacter cloacae , a normal gut flora, is responsible for increasing nosocomial infections and antibiotic resistance. This microorganism causes sepsis and meningitis mainly in immunocompromised patients [ 83 - 85 ]. Our records regarding E. cloacae reached 6.66% from intestinal content, and deep pharyngeal swab and kidney predispose the contamination of food and places.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Gram-negative bacteria, Enterobacter cloacae , a normal gut flora, is responsible for increasing nosocomial infections and antibiotic resistance. This microorganism causes sepsis and meningitis mainly in immunocompromised patients [ 83 - 85 ]. Our records regarding E. cloacae reached 6.66% from intestinal content, and deep pharyngeal swab and kidney predispose the contamination of food and places.…”
Section: Discussionmentioning
confidence: 99%
“…Our records regarding E. cloacae reached 6.66% from intestinal content, and deep pharyngeal swab and kidney predispose the contamination of food and places. The threats of genus Enterobacter may extend to high mortality rates in premature infants [ 85 ]. Hunter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fata et al reported a fatal case of myositis in a neutropenic patient (133). E. cloacae has been implicated in cases of endophthalmitis (134), brain abscess (135), meningitis (136), spondylodiscitis (137), and endocarditis (138).…”
Section: Human Reservoirs and Hospital-acquired Infectionsmentioning
confidence: 99%
“…Chauhan and ter Haar developed a HIFU treatment system named FUSBOT which combined with the robotic arm to achieve the stability and the positioning accuracy of HIFU focal point. According to their study, the navigation errors were within 0.5 mm [16, 17]. Masamune et al developed another HIFU positioning robot treatment system which integrated the HIFU transducer, ultrasound probe, and a robotic arm (which has 4 degrees of freedom) for fetal sacrococcygeal teratoma treatment.…”
Section: Introductionmentioning
confidence: 99%